1973
DOI: 10.1351/pac197334030553
|View full text |Cite
|
Sign up to set email alerts
|

The plant ferredoxins and their relationship to the evolution of ferredoxins from primitive life

Abstract: The first few ferredoxins were isolated, more or less simultaneously, from Clostridurn and spinach. These non-haem, ironcontaining oxidoreductases had almost the same low redox potential and both could catalyse the photoreduction of NADP by chloroplasts. but differed in molecular weight and in the number of iron atoms they contained. Since that time nearly forty more ferredoxins have been isolated from all classes of organisms. These fall into four categories containing respectively 2, 4, 6 or 8 atoms of iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The purified recombinant proteins were red-brown in colour and the absorption spectra of both proteins displayed maxima at 330 nm, 423 nm, and 466 nm (Figure 3b), which are characteristic of plant ferredoxins [21]. These data show both pectocins M1 and M2 contain a [2Fe-2S] cluster.…”
Section: Resultsmentioning
confidence: 80%
“…The purified recombinant proteins were red-brown in colour and the absorption spectra of both proteins displayed maxima at 330 nm, 423 nm, and 466 nm (Figure 3b), which are characteristic of plant ferredoxins [21]. These data show both pectocins M1 and M2 contain a [2Fe-2S] cluster.…”
Section: Resultsmentioning
confidence: 80%
“…Amino acid compositions of Sambucus and Leucaena ferredoxin L, lysozyme; R, ribonuclease; F1 and F2, samples of Sumbucus ferredoxin from two different preparations.values suggest that two iron atoms are present in one molecule of Sambucus ferredoxin, as in all wellcharacterized plant ferredoxins(24). Together with the results of the EPR spectrum, this suggests the active centre ofSambucus ferredoxin to be the same as in other plant chloroplast ferredoxins.Amino Acid CompositionThe amino acid composition of Sambucus ferredoxin is detailed inTable 1.…”
mentioning
confidence: 65%
“…3) of Sambucus ferredoxin is typical of a plant-type ferredoxin containing two atoms of iron and two atoms of labile sulphur per molecule (24). The principal apparent g values at 20°Careg,r = 1.894,gr = 1.957, andg, = 2.046.…”
Section: Spectral Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study has strongly suggested the commonness of the blue-green algal ferredoxin and those of green plants including green algae. Several other blue-green algal ferredoxins have been shown to have characteristics of the typical chloroplast-type ferredoxin [7][8][9][10][11][12] and their amino acid compositions have suggested the common origin of these and green plant ferredoxins.…”
Section: Introductionmentioning
confidence: 99%